Determining The Effects Of Adopting Green Construction Site Practices On Project Performance In Nigeria - Hilary, Omatule Onubi (2020)
The negative effects of traditional construction practices on the environment has resulted in increased advocacy for green construction site practices to be adopted in developing countries. Despite the advocacy for the adoption of green construction site practices, the rate of adoption is still low and this has been attributed to uncertainties regarding project performance, and lack of attention given to project complexity. This study is aimed at determining the effects of adopting green construction site practices on project performance taking into consideration project complexity. The deductive research approach was adopted using correlational research design, and the survey method was used for data collection. The questionnaires were self-administered. Non-probability sampling technique was used in this study for a population of 227 projects and 168 usable responses were collected with a response rate of 78%. The collected data were analysed using descriptive statistics (mean score) and the partial least squares-structural equation modelling. All the green construction site practices had high rates of adoption. It was observed that all the green construction practices studied had significant effects on project performance of construction projects except for site layout planning and development. The findings also indicate that project complexity moderates 2 out of the 6 hypothesized moderating relationships but weakens the relationship. The highest moderating effect is the effect of project complexity on the relationship between stormwater management and project performance.